Odpowiedź :
No liczę na jakieś serduszko chociaż :/
a)4x+15=-5/-4x
15=-4x-5/+5
20=-4x/-4
-5=x
b)
2x+7=4x-3/+3
2x+10=4x/-2x
10=2x/2
5=x
c)
-2(x+3)+4(2x+3)=-6
-2x-6+8x+12=-6
6x+6=-6/-6
6x=-12/6
x=-2
d)
x-(7+2x)=2(x-1)+1
x-7-2x=2x-2+1/-2x
x-7-4x=-1/+7
-3x=6/-3
x=-2
Przepisz sobie, reszte przykładów już dopisuje
e)
[tex]\frac{x}{2} -\frac{3}{4} =\frac{7}{8} +\frac{x}{4}/*8 \\\\4x-6=7+2x/-2x\\2x-6=7/+6\\2x=13/2\\x=6,5[/tex]
f)
[tex]\frac{x+5}{3}-5=x-2/*3\\x+5-15=3x-6\\x-10=3x-6/+6\\x-4=3x/-x\\-4=2x\\x=-2[/tex]
g)
[tex]\frac{x+4}{5} +\frac{2x+9}{10}=\frac{-2-x}{2} /*10\\2x+8+2x+9=-10-5x\\4x+17=-10-5x/+10\\4x+27=-5x/-4x\\27=-9x/-9\\-3=x[/tex]
Odpowiedź:
a)4x+15=-5
4x=-5-15
4x=-20/:4
x=-5
b)2x+7=4x-3
2x-4x=-3-7
-2x=-10/:(-2)
x=5
c)-2(x+3)+4(2x+3)=-6
-2x-6+8x+12=-6
6x=-6-6
6x=-12
x=-2
d)x-(7+2x)=2(x-1)+1
x-7-2x=2x-2+1
-x-2x=-1+7
-3x=6.:(-3)
x=-2
e)[tex]\frac{x}{2}-\frac{3}{4}=\frac{7}{8}+\frac{x}{4}/*8[/tex]
[tex]4x-6=7+2x[/tex]
4x-2x=7+6
2x=13/:2
x=6,5
f)[tex]\frac{x+5}{3}-5=x-2/*3[/tex]
x+5-15=3x-6
x-3x=-6+10
-2x=4/:(-2)
x=-2
g)[tex]\frac{x+4}{5}+\frac{2x+9}{10}=\frac{-2-x}{2}/*10[/tex]
2x+8+2x+9=-10-5x
4x+5x=-10-17
9x=-27/:9
x=-3
Szczegółowe wyjaśnienie: